The Position of Alexey Rumyantsev: An Unspoiled Scientific Obituary - Dmitry Rogozin (Journal of Economic Sociology, 2025)
This article is dedicated to the life and scientific work of Alexei Matveevich Rumyantsev (1905−1993), an outstanding Soviet scholar in social sciences. The author describes Rumyantsev’s path from a young Leninist to a high-ranking party official and academician of the USSR Academy of Sciences. Special attention is given to his contribution to the development of Soviet sociology and political economy. Rumyantsev became the first head of the Institute of Concrete Sociological Research (ICSIR) and laid the foundations for objective Marxist-Leninist applied sociology. Under his leadership, key directions for the development of sociological research were formed, including social forecasting and analysis of urbanization processes. The author emphasizes the dual nature of Rumyantsev’s personality - he was both a passionate follower of Marxism-Leninism and a liberal intellectual who promoted free thinking among young scientists. His work at the intersection of dogmatic Marxism and a liberal approach played an important role in shaping a unique model of Soviet sociology. The article presents numerous valuable testimonies from contemporaries about Rumyantsev’s professional and personal qualities. He is characterized as a talented organizer of the scientific process who created a unique atmosphere at ICSIR, where strict party requirements coexisted with scientific inquiry. The article also examines criticism of Maoism, studies of primitive society, and other significant scientific interests of Rumyantsev. Particular emphasis is placed on his role in international cooperation among Soviet sociologists.